2013
DOI: 10.11599/germs.2013.1046
|View full text |Cite
|
Sign up to set email alerts
|

Association between inbreeding coefficient and susceptibility to HIV-1 infection, a case-control study

Abstract: Introduction Consanguinity has been associated with adverse health outcomes. The objective of the present study was to assess the association between parental consanguinity and risk of infection with human immunodeficiency virus type-1 (HIV-1).Methods Data were collected from 333 HIV-1 infected individuals referred to a local health center in Shiraz (southern Iran). A total of 999 healthy individuals frequency matched with the cases according to their sex and age were also studied, as a control group.Results P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
6
1
Order By: Relevance
“…Consanguinity also increases the probability of having homozygosity as it increases the rate of acquiring two copies of the defected recessive alleles from the common ancestor [ 13 ]. However, there are other studies that described a reverse association between consanguinity and some diseases and cancers [ 14 16 ]. This means that consanguinity has complicated interactions that might either increase or decrease susceptibility of certain cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Consanguinity also increases the probability of having homozygosity as it increases the rate of acquiring two copies of the defected recessive alleles from the common ancestor [ 13 ]. However, there are other studies that described a reverse association between consanguinity and some diseases and cancers [ 14 16 ]. This means that consanguinity has complicated interactions that might either increase or decrease susceptibility of certain cancers.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 5 14 However, there were some reports that described a negative association between consanguinity and risk of diseases. 15 17 A negative association was reported between the susceptibility to infection with HIV-1 and inbreeding coefficient. 17 Based on an ecologic study the mean of inbreeding coefficient (at the population level; α) is negatively associated with age-standardized mortality rate due to breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“… 15 17 A negative association was reported between the susceptibility to infection with HIV-1 and inbreeding coefficient. 17 Based on an ecologic study the mean of inbreeding coefficient (at the population level; α) is negatively associated with age-standardized mortality rate due to breast cancer. This means that the countries with a high level of consanguinity show a low level of age-standardized mortality rates due to breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together it might be concluded that consanguinity has social advantages. On the other hand, consanguineous marriages are associated with increased risk of recessive traits and also it might be associated with many multifactorial diseases [4,[10][11][12][13][14]. However, activities for reduction of consanguinity which is culturally favored in population, without attention to its social reflections, are not recommended.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of consanguinity is influenced by several factors including demographic, religious, cultural and socio-economic factors [4][5][6][7][8]. Many studies indicated that consanguineous marriages are associated with increased risk of recessive traits [9,10] and also it might be associated with many multifactorial diseases among their offspring [4,[10][11][12][13][14]. It should be noted that the associations between consanguineous marriages and susceptibility to multifactorial disorders are controversial.…”
Section: Introductionmentioning
confidence: 99%